2005
DOI: 10.1021/ol0522236
|View full text |Cite
|
Sign up to set email alerts
|

A Triple Diene-Transmissive Diels−Alder Strategy To Build the Quassinoid Framework

Abstract: [chemical reaction: see text]. An advanced intermediate to the highly oxygenated triterpene quassinoids was prepared in 14 steps from tetrahydrofuran. The key steps are three diene-transmissive Diels-Alder cycloadditions. Several features of this synthesis are noteworthy, including a successful Mitsunobu reaction on an allenylic alcohol, a rare [4 + 2] cycloaddition involving an enethiol ether dienophile, and complete control over all 10 chiral centers created.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 15 publications
0
12
0
3
Order By: Relevance
“…Selbstverständlich lassen sich auch Heteroatome in die π‐Systeme von Dien‐ und Dienophilkomponente einbauen. Und in der Tat haben Spino197, 198 und Saito und Mitarbeiter199 in mehreren wichtigen und eleganten Studien über die Verwendung von “Heterodendralenen” berichtet. Mit einer Ausnahme (siehe Abschnitt 10) haben wir Beispiele dieser Art in diesem Aufsatz unberücksichtigt gelassen – weil wir uns vorwiegend auf die Oligoene konzentrieren wollen.…”
Section: Dien‐transmissive Diels‐alder‐reaktionen Von Dendralenenunclassified
See 1 more Smart Citation
“…Selbstverständlich lassen sich auch Heteroatome in die π‐Systeme von Dien‐ und Dienophilkomponente einbauen. Und in der Tat haben Spino197, 198 und Saito und Mitarbeiter199 in mehreren wichtigen und eleganten Studien über die Verwendung von “Heterodendralenen” berichtet. Mit einer Ausnahme (siehe Abschnitt 10) haben wir Beispiele dieser Art in diesem Aufsatz unberücksichtigt gelassen – weil wir uns vorwiegend auf die Oligoene konzentrieren wollen.…”
Section: Dien‐transmissive Diels‐alder‐reaktionen Von Dendralenenunclassified
“…Der Arbeitskreis von Spiro hat mehrere Arbeiten über eine DTDA‐Strategie veröffentlicht, bei der auf eine intermolekulare Hetero‐Diels‐Alder‐Reaktion eine intramolekulare Diels‐Alder‐Reaktion folgt und das Quassinoidgerüst erhalten wird 197. 198 Vor Kurzem haben diese Autoren die Herstellung eines bereits hochentwickelten Intermediats auf dem Wege zu Quassinoiden beschrieben ( 429 ; Schema ) 197. Dabei wird im ersten Schritt durch eine Hetero‐Diels‐Alder‐Reaktion aus dem Oxa‐2,3‐cyclo[3]dendralen 427 und Ethylvinylether das Addukt 428 hergestellt, das nachfolgend in einer intramolekularen Diels‐Alder‐Reaktion den Pentacyclus 429 als einziges Isomer ergibt.…”
Section: Zusammenfassung – Perspektiven – Anwendungenunclassified
“…J ‐coupling values were in agreement in those reported by Bernard, who had confirmed the trans ‐configuration by 2D NMR and NOESY experiments. After formation of the central moiety, the sulfide is installed over three steps (ii‐iv), by reduction, Mitsunobu reaction [13] and deprotection/allylation to yield 15 . The challenging step of the synthesis was the subsequent deprotection of the para ‐methoxy benzyl (PMB) group.…”
Section: Methodsmentioning
confidence: 99%
“…Since the separation turned out to be quite difficult, we opted for propenyllithium. [14] To our surprise, the high order cuprate this time gave the best results and compound 12 b was obtained in 52 % yield (Scheme 2). We also observed that the cis reactant was only poorly added to diketone 11.…”
mentioning
confidence: 91%